(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Three lactic acid bacteria (LAB) isolates which demonstrated probiotic properties were obtained from chicken intestine. The isolates demonstrated good tolerance to acidic pH 3, 0.3% bile salts and strong adhesion to Caco-2 cells. These isolates also showed antagonistic activity against pathogenic E. coli (078:K80), Salmonella enterica serovar Typhimurium, C. perfringens (Type A), Salmonella enterica serovar Enteritidis, E. faecium (FM3), E. faecalis (E227). All three isolates had high inhibition zone (> 6 mm) against E. coli 078:K80 and Salmonella enterica serovar Typhimurium and were susceptible to antibiotics gentamicin, kanamycin, streptomycin, tetracycline, erythromycin, clindamycin, chloramphenicol and ampicillin. These isolates were identified by using 16S rRNA sequencing technique and as two L. salivarius and one L. reuteri with accession number MH375403, MH375402 and MH375404, respectively.